Strategi Promosi Sekolah oleh Humas melalui Platfrom Digital di SMP Negeri 9 Palembang - Khusnul Khotimah; Ade Akhmad Saputra (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to describe public relations strategies for promoting school programs through digital media to increase interest among new students at SMP Negeri 9 Palembang. The study employs a descriptive qualitative approach. Research subjects were selected using purposive sampling, including the principal, the vice principal for public relations, teachers, students, and parents. Data collection was conducted through observation, in-depth interviews, and document analysis. Data analysis utilized the Miles, Huberman, and Saldana model, which includes data collection, data condensation, data presentation, and drawing conclusions. Data validity was tested through triangulation of sources and techniques. The research results indicate that the public relations strategies of SMP Negeri 9 Palembang in digital promotion encompass four aspects of the marketing mix: (1) marketing the school’s flagship programs—such as extracurricular activities and student achievements—through visual content on Instagram, Facebook, and YouTube; (2) transparently communicating information about free education via social media as an attraction for the public; (3) optimizing the accessibility of school information via the website, social media, and WhatsApp; and (4) planned and consistent digital promotional activities with a posting frequency of three to four times per week. These strategies have proven effective in increasing interest and the number of new student applicants at SMP Negeri 9 Palembang. Keywords: Public Relations Strategy, Digital Media, School Promotion, Interest of Prospective Students